1996
DOI: 10.1111/j.1476-5381.1996.tb15771.x
|View full text |Cite
|
Sign up to set email alerts
|

Selectivity and activity of adenine dinucleotides at recombinant P2x2 and P2Y1 purinoceptors

Abstract: 1 Adenine dinucleotides (ApXA, x = 2 -6) are naturally-occurring polyphosphated nucleotidic substances which are found in the CNS and are known to be released in a calcium-dependent manner from storage vesicles in brain synaptosomes. The selectivity and activity of adenine dinucleotides for neuronally-derived recombinant P2 purinoceptors were studied using P2x2 and P2Yj subtypes expressed

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
56
1

Year Published

2000
2000
2004
2004

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(61 citation statements)
references
References 48 publications
4
56
1
Order By: Relevance
“…Diadenosine polyphosphates were also found to be potent and full agonists in cells overexpressing the human P2Y 2 receptor (Lazarowski et al, 1995). Also, the avian P2Y 1 receptor is sensitive to Ap 4 A, presenting EC 50 values in the nanomolar range (Pintor et al, 1996). Important differences have been observed on native P2Y 1 receptors, where diadenosine tetraphosphate behaved as an antagonist in clear contrast to the behavior of this dinucleotide in cloned P2Y 1 receptors (Vigne et al, 2000).…”
mentioning
confidence: 92%
“…Diadenosine polyphosphates were also found to be potent and full agonists in cells overexpressing the human P2Y 2 receptor (Lazarowski et al, 1995). Also, the avian P2Y 1 receptor is sensitive to Ap 4 A, presenting EC 50 values in the nanomolar range (Pintor et al, 1996). Important differences have been observed on native P2Y 1 receptors, where diadenosine tetraphosphate behaved as an antagonist in clear contrast to the behavior of this dinucleotide in cloned P2Y 1 receptors (Vigne et al, 2000).…”
mentioning
confidence: 92%
“…For example, receptors that are activated by Ap 4 A but not other diadenosine nucleosides have been described in recombinant rat P2X 2 receptors, expressed in Xenopus laevis oocytes. This receptor is activated by Ap 4 A, but not Ap 2 A, Ap 3 A, or Ap 5 A (Pintor et al, 1996;Wildman et al, 1999). The MM39 cell line, derived from human tracheal gland epithelium, possesses a native receptor that is also sensitive to Ap 4 A but not Ap 3 A or Ap 5 A (Saleh et al, 1999).…”
Section: Downloaded Frommentioning
confidence: 99%
“…In particular diadenosine triphosphate (Ap 3 A), diadenosine tetraphosphate (Ap 4 A), diadenosine pentaphosphate (Ap 5 A), Ap 6 A, and Ap 7 A are found in exocytotic vesicles, such as those in nerve terminals, adrenal medullary chromaffin cells, and platelets (Flodgaard and Klenow, 1982;Rodriguez del Castillo et al, 1988;Pintor et al, 1992aPintor et al, ,b,c, 1997Schlü tter et al, 1994;Pintor and Miras-Portugal, 1995;Jankowski et al, 1999), and diadenosine pyrophosphate (Ap 2 A) has recently been identified in secretory granules of cardiac myocytes (Luo et al, 1999). They have diverse actions in peripheral and central tissues because of their roles as extracellular signal molecules (Hoyle, 1990;Pintor et al, 1996;Kisselev et al, 1998;Hoyle et al, 2001).…”
mentioning
confidence: 99%
“…We performed similar experiments with PC12 cells, which possess P2X2 and P2Y2 receptors but not the P2X7 receptor. In PC12 cells, 100 mM UTP induces [Ca 2+ ]i elevation via the P2Y 2 receptor (18,19) and subsequent application of 100 mM ATP in the presence of UTP induces [Ca 2+ ]i elevation via the P2X2 receptor (14,20 Kaiho et al (3) reported that anions inhibit ATP-binding to the receptor and that the order of inhibition correlates with the hydration energy of each anion. ATP 4-has been reported to be the effective agonist form of ATP for the P2X7 receptor (21).…”
Section: Replacing External CLmentioning
confidence: 99%